Exploration of probiotic attributes in lactic acid bacteria isolated from fermented Theobroma cacao L. fruit using in vitro techniques - Nandha, Mausamy C.; Shukla, Rachana M. (Frontiers in Microbiology, 2023)
Probiotics are known for their health-promoting properties and are recognized as beneficial microorganisms. The current investigation delves into the isolation and comprehensive in vitro characterization of lactic acid bacteria (LAB) obtained from the Indian-origin Theobroma cacao L. Forastero variety to assess their potential as probiotic candidates. Eleven LAB isolates were obtained, and among them, five exhibited classical LAB traits. These five isolates underwent rigorous in vitro characterization to evaluate their suitability as probiotics. The assessments included resilience against acid and bile salts, which are crucial for probiotic viability. Additionally, the isolates were subjected to simulated gastric and pancreatic fluids and lysozyme exposure to assess their survival rates. Auto- aggregation, co-aggregation, hydrophobicity, and exopolysaccharide production were also examined. The inhibitory potential of α-glucosidase, an enzyme related to glucose metabolism, was measured, and antioxidant activity was evaluated using DPPH and ABTS assays. A safety assessment was conducted to confirm the non-pathogenic nature of the isolates. Among the five isolates, CR2 emerged as a standout candidate with maximal bile salt hydrolase activity, phenol resistance, and lysozyme resistance. CR2 and CYF3 exhibited notable survival rates under simulated conditions. The isolates displayed variable degrees of auto-aggregation, co-aggregation, and hydrophobicity. CR2 exhibited the highest exopolysaccharide production (0.66 mg/mL), suggesting diverse applications in the food industry. CR2 also demonstrated the highest inhibition rate against α-glucosidase (56.55%) and substantial antioxidant activity (79.62% DPPH, 83.45% ABTS). Safety assessment confirmed the non- pathogenic nature of the isolates. Molecular characterization identified CR2 as Lactococcus lactis subsp. lactis and CYF3 as Limnosilactobacillus fermentum. Both strains exhibited commendable probiotic and technological attributes, positioning them as promising candidates for functional foods and beyond. This study provides valuable insights into the in vitro characterization of LAB isolated from Indian Theobroma cacao L., highlighting their potential as probiotic candidates with advantageous traits, including survival in hostile conditions, beneficial enzymatic activities, bioactivity, and other essential attributes.